2012
DOI: 10.1249/mss.0b013e31823378b1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Competition on Performance and Pacing during Cycling Exercise

Abstract: HH competition encourages participants to increase their performance. This occurs primarily via an increased anaerobic energy yield, which seems to be centrally mediated, and is consistent with the concept of a physiologic reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
134
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(161 citation statements)
references
References 26 publications
22
134
2
3
Order By: Relevance
“…Results showed that deception trials were significantly faster and had a higher mean power output than both an accurate feedback condition and the baseline performance, suggesting that the deception of intensity based on a previous trial was beneficial to TT performance. Corbett et al [11] also used the presence of a simulated competitor, deceiving participants that it was an athlete of similar ability when it was in fact their own baseline performance, and further supported Stone et al's [12] findings. A faster time to completion and alteration in pacing strategy in a 2 km cycling TT were reported in the trial with head-to-head competition, in comparison to familiarisation and ride-alone trials.…”
Section: Continuous Visual Feedbackmentioning
confidence: 54%
See 4 more Smart Citations
“…Results showed that deception trials were significantly faster and had a higher mean power output than both an accurate feedback condition and the baseline performance, suggesting that the deception of intensity based on a previous trial was beneficial to TT performance. Corbett et al [11] also used the presence of a simulated competitor, deceiving participants that it was an athlete of similar ability when it was in fact their own baseline performance, and further supported Stone et al's [12] findings. A faster time to completion and alteration in pacing strategy in a 2 km cycling TT were reported in the trial with head-to-head competition, in comparison to familiarisation and ride-alone trials.…”
Section: Continuous Visual Feedbackmentioning
confidence: 54%
“…Stone et al [12] and Corbett et al [11] both showed that in the final 10% and 50% of the deception trials, respectively, there was a greater contribution from anaerobic energy sources that resulted in the increases in power output and faster completion time. Alternatively, Parry et al [6] stated that a shallower rate of RPE increase, and an increase in workrate to complete the exercise sooner, resulted in an increase in power output.…”
Section: Continuous Visual Feedbackmentioning
confidence: 99%
See 3 more Smart Citations